The "terminal line": a novel sign for the identification of distal mesorectum end during TME for rectal cancer. (21st September 2022) - Ghareeb, Waleed M; Wang, Xiaojie; Zhao, Xiaozhen; Xie, Meirong; Emile, Sameh H; Shawki, Sherief; Chi, Pan
Abstract: Background: Although the clinical importance of complete, intact total mesorectal excision (TME) is the widely accepted standard for decreasing local recurrence of rectal cancer, the residual mesorectum still represents a significant component of resection margin involvement. This study aimed to use a visible intraoperative sign to detect the distal mesorectal end to ensure complete inclusion of the mesorectum and avoid unnecessary over-dissection. Methods: The distal mesorectum end was investigated retrospectively through a review of 124 operative videos at the Union Hospital of Fujian Medical University (Fujian, China) and Cleveland Clinic (Ohio, USA) by two independent surgeons who were blinded to each other. Furthermore, 28 cadavers and 44 post-operative specimens were prospectively examined by hematoxylin and eosin (H&E) staining and Masson's staining to validate and confirm the findings of the retrospective part. Univariate and multivariate analyses were carried out to detect the independent factors that can affect the visualization of the distal mesorectal end. Results: The terminal line (TL) is the distal mesorectal end of the transabdominal and transanal TME (taTME) and appears as a remarkable pearly white fascial structure extending posteriorly from 2 to 10 o'clock. Histopathological examination revealed that the fascia propria of the rectum merges with the presacral fascia at the TL, beyond which the mesorectum ends, with no further downward extension. In the retrospective observation, the TL was seen in 56.6% of transabdominal TME and 56.0% of taTME operations. Surgical approach and tumor distance from the anal verge were the independent variables that directly influenced the detection of the TL ( P  =   0.03 and P  =   0.01). Conclusion: The TL is a visible sign where the transabdominal TME should end and the taTME should begin. Recognition of the mesorectal end may impact the certainty of complete mesorectum inclusion. Further clinical trials are needed to confirm the preliminary findings.